Effects of the COVID-19 pandemic on the global health of women aged 50 to 70 years - Lima, Joao G. Ribeiro de; Abud, Gabriela F. [UNESP]; Freitas, Ellen C. de [UNESP]; Junior, Carlos R. Bueno (Elsevier B.V., 2021)
Aim/background: The most recent pandemic caused by the new coronavirus disease (COVID-19) urged dramatic changes in people & rsquo;s lives. Potentially, the COVID-19 pandemic affects physical and mental health as well as behavioral and social aspects. However, the direct impacts of the COVID-19 pandemic on health-related parameters are not yet known. The present study aimed to evaluate the effect of 16 weeks during the COVID-19 pandemic on health-related parameters of physically inactive women aged 50 to 70 years. Methods: Thirty-four physically inactive women participated in the study. We performed tests to evaluate aerobic capacity and muscle strength, anthropometric measurements, blood pressure (BP), blood parameters, diet, and physical activity levels. All evaluations were carried out before and 16 weeks after the initial phase of the COVID19 pandemic in Brazil (i.e., from March to July 2020). Results: Systolic BP (p < .0001; effect size (ES) = 0.62), diastolic BP (p < .0001; ES = 0.71), grip strength of the right (p < .05; ES = 0.43) and left hand (p < .05; ES = 0.49), performance in six-minute walk test (p < .05; ES = 0.46), free time physical activity levels (p < .05; ES = 0.40), domestic physical activity levels (p < .05; ES = 0.39), platelet count (p < .0001; ES = 0.48), and mean corpuscular hemoglobin concentration (p < .0001; ES = 1.14) reduced in comparison to the period before the pandemic. In contrast, glycated hemoglobin levels (p < .0001; ES = 0.77), triglycerides (p < .05; ES = 0.40), and insulin levels (p < .05; ES = 0.60) increased in comparison to the period before the pandemic. Conclusion: The COVID-19 pandemic negatively impacted the general health status of physically inactive women aged 50 to 70, potentially increasing their susceptibility to comorbidities, such as type 2 diabetes and hypertriglyceridemia.
Keywords: Fitness; Blood parameters; Physical inactivity; SARS-CoV-2; Aging